2014
DOI: 10.1007/s12272-014-0481-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved oral bioavailability of capsaicin via liposomal nanoformulation: preparation, in vitro drug release and pharmacokinetics in rats

Abstract: This study innovatively prepared an effective capsaicin-loaded liposome, a nanoformulation with fewer irritants, for oral administration. The in vitro and in vivo properties of the liposomal encapsulation were investigated and the potential possibility of oral administration evaluated. The liposomal agent composed of phospholipid, cholesterol, sodium cholate and isopropyl myristate was prepared using film-dispersion method. A level A in vitro-in vivo correlation (IVIVC) was established for the first time, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…Structurally, phospholipid resembles the lipid membrane of living cells. The amphiphilic characteristic allows them to form organized structures, such as carriers or membranes of lipid bilayer, when injected into an aqueous environment (stirring) [12]. Phospholipid based carries reveled features include higher encapsulation efficiency (EE) and oral bioavailability, non-toxicity, and better biocompatibility and stability compared with traditional liposomes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, phospholipid resembles the lipid membrane of living cells. The amphiphilic characteristic allows them to form organized structures, such as carriers or membranes of lipid bilayer, when injected into an aqueous environment (stirring) [12]. Phospholipid based carries reveled features include higher encapsulation efficiency (EE) and oral bioavailability, non-toxicity, and better biocompatibility and stability compared with traditional liposomes [13].…”
Section: Introductionmentioning
confidence: 99%
“…The particles also resulted in 27-fold higher AUC than that of curcumin powder in healthy human volunteers, theracurmin (30 mg) when administered orally [143]. Capsaicin is also able to be encapsulated in liposome, which shows improved oral bioavailability [127].…”
Section: Bioavailability Safety Tolerability and Pharmacokineticsmentioning
confidence: 99%
“…Capsaicin is also known to have low bioavailability, which is associated with poor water solubility and a short half-life [126,127]. On the other hand, it has been reported that over 90% of capsaicin can be absorbed rapidly and reach the peak concentration at 1 h after administration in rats [128].…”
Section: Bioavailability Safety Tolerability and Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, developing a novel oral preparation of capsaicin has become imperative. In light of this, recently, a number of formulation strategies including nanoemulsion (20), liposome (21), and micelle (22) have been employed to solubilize and to enhance the oral bioavailability while without the effect of sustained release. In spite of these developments, exploiting the full clinical application of capsaicin is far from being optimized.…”
Section: Introductionmentioning
confidence: 99%